Impact Assessment of Covid-19 Lockdown on Teaching and Learning in Federal College of Education, Zaria (Global Journal of Human-Social Science, 2021)
By late 2019, the world experienced the emergence and surge in coronavirus that was later described as health pandemic. This has led to colossal damage in many sectors of the global system. All countries affected by the pandemic adopted many strategies to curb the spread and mitigate the further human lives loss. Lockdown or movement restrictions as one of the protocols were imposed. The lockdown affected all sectors of the economy, including education, as academic institutions were closed. The study, therefore, accessed the impact of the lockdown on teaching and learning in Federal College of Education Zaria. The study adopted a descriptive survey design, and 120 respondents comprising 51 academic staff, 25 non-academic staff, and 44 students were randomly sampled for the administration of the questionnaire. The questionnaire used was self-structured and designed by the researchers tagged: C-19LTL-FCE-Zaria. Data collected were analyzed using quantitative descriptive statistical tools of mean and standard deviation and regression for testing the hypothesis. The findings show that controlling further spread of the coronavirus among citizens was among the reasons for the enforcement of covid-19 lockdown in Kaduna State.
Keywords: covid-19; lockdown; teaching; and learning